Cost savings of outpatient versus inpatient hip and knee arthroplasty in Ontario, Canada - Steven Habbous; Sisira Sarma; Brent Lanting; James Waddell; Erik Hellsten (PLoS ONE, 2025)
Introduction Hip and knee replacement surgery is one of the most commonly performed elective procedures, accounting for significant healthcare costs and resource utilization. In recent years, the proportion of hip and knee arthroplasties performed in outpatient settings has grown rapidly. Although the safety and effectiveness of outpatient vs. inpatient hip and knee arthroplasty have been documented in the literature, estimates of health system cost-savings in Canada are limited. Methods We employed a population-based retrospective cohort study design. We obtained data on patients aged 18–105 years who underwent hip or knee replacement surgery in both inpatient and outpatient settings in Ontario, Canada between 2018/19 and 2022/23. Patients who underwent outpatient hip and knee arthroplasty were matched to inpatient cases using a propensity score based on age, sex, comorbidity, area-level sociodemographic factors, total/partial replacement, and surgery date. We analyzed cost data that included hospitalization and ambulatory care visits, physician billing, home care, and oral medications. We utilized generalized linear models to identify the best fit regression model and estimated the average cost-savings associated with outpatient versus inpatient arthroplasty during the preoperative (30-days before surgery), perioperative (surgery + 30 days), 1–6-month postoperative, 6–12-month postoperative, 12–24-month postoperative, and 24–36-month postoperative periods. The costs were reported in 2023 Canadian dollars. Results A total of 35,894 hip arthroplasty patients and 49,597 knee arthroplasty patients were included in our analysis. During the perioperative period, outpatient arthroplasty was less costly than inpatient arthroplasty for hip replacement by $3,859 (95% CI -$4045, -$3745) and for knee replacement by $3,966 ($-4080, $-3851). Over 3 years of follow-up, outpatient arthroplasty was less costly than inpatient arthroplasty for hip replacement by $7058 (-$8086, -$6031) and for knee replacement by $7043 (-$7842, -$6243). Conclusion Outpatient hip and knee arthroplasty is cost-saving both during and beyond the perioperative period in comparison with similar patients who undergo inpatient arthroplasty in Ontario. Policies should be put in place to incentivize continued uptake of outpatient arthroplasty, which we estimate could save the Ontario healthcare system up to $98 million per year.